Nickel-Catalyzed Reductive Allylation of Aldehydes with Allyl Acetates - Suzuki, Hiroyuki; Yamaguchi, Eiji; Itoh, Akichika (Synthesis, 2020)
Carbonyl allylation reactions constitute an important step in the formation of carbon–carbon reactions, and involve various related reactions that chiefly use allylmetal reagents. This report presents a nickel-catalyzed carbonyl allylation reaction using allyl acetate, which produces homoallyl alcohols in moderate to good yields, as an efficient methodology under reductive coupling conditions.
Keywords: reductive allylation; nickel complex; allyl acetate; carbonyl addition; transition-metal catalysis